Between the architectural program and beauty - Mendes, P. (2020)
Utility and beauty are two architectural design foundation stones. Over time, architecture has developed multiple combinations and interpretations of these two elements. Despite all the contextual and cultural changes, which may differentiate distinct designs, the architectural practice can be delineate as laying at the contextual root, rather than providing a direct response to procedure and standards. The overall practice of architecture embraces a synthesis of a wide range of elements interpreted in different perspectives throughout history. The practice shapes specific responses transforming and adapting places, spaces, techniques and materials to different contexts. The investigation is part of an ongoing process centered on themes and issues related to architectural design. The research guideline focusses on the What and How of architectural design. In the present paper the topics arise from a text of Álvaro Siza: „Beauty, the absolute condition of functionality” (Siza, 2018). From Álvaro Siza statement beauty and function are considered inseparable in building good architecture synthesis. The paper explores the relation between the architectural program and beauty. Frequently these two components are considered incompatible and opposite, although other perspectives ought to be explored.The dialectic overlap and boundaries between the architectural program and beauty will be inquired. The perspective allows identifying operative relations, far from the notion of contradiction or opposition. The investigation context is grounded in the universe of architectural design. On one side it can be found beauty, characterised by an idealistic desire for perfection and truth. We are dealing with an immaterial universe. On the other, the architectural program stands for the architectural practical and useful attributes of use. Through a holistic methodology it is expected an operative input to architectural design practice. In the same direction we hope to contribute for the enlargement of the range of level of self-reflective practice.